Enforcement of Labor Regulation and Firm Size - Almeida, Rita; Carneiro, Pedro (2012)
This paper investigates how the enforcement of labor regulation affects firm size and other firm characteristics in Brazil. We explore firm level data on employment, capital, and output, city level data on economic characteristics, and new administrative data measuring enforcement of regulation at the city level. Since enforcement may be endogenous, we instrument this variable with the distance between the city where the firm is located and surrounding enforcement offices, while controlling for a rich set of city characteristics (such as past levels of informality in the city). We present suggestive evidence of the validity of this instrument. We find that stricter enforcement of labor regulation constrains firm size, and leads to higher unemployment.